Building resistance : children, tuberculosis, and the Toronto sanatorium - Burke, Stacie (Stacie D. A.) (desLibris. Books collection., 2018)
"In 1882, Robert Koch determined that tuberculosis was an infectious disease caused by a bacterium. In Canada, tuberculosis was a widespread, endemic disease and many children were infected in their youth, often within their family homes. Ongoing concerns led to the rise of modern, scientific hospitals specialized in the treatment of tuberculosis, including the Toronto sanatorium which opened in 1904 on the outskirts of the city. Lacking antibiotic treatments until the 1940s, the early sanatorium era was defined by the principles of resistance building, recognizing that the body itself possessed a potential to overcome tuberculosis through rest, nutrition, and fresh air. Over time, various surgeries were added to the medical repertoire, all intended to assist the body in building resistance. Belief in modern medicine positioned the Toronto sanatorium as a place of perseverance and hope. Situated in the era before streptomycin, Building Resistance explores children's diverse experiences with tuberculosis infection, disease, hospitalization, and treatment. Grounded in a descriptively rich and thick qualitative case study methodology, and based on archival research, the book examines children's experiences at the Toronto sanatorium between 1909 and 1950. In Building Resistance Stacie Burke questions how tuberculosis infection and disease impacted on the bodies, families, and lives of children. The tuberculosis experience is approached holistically, as a biosocial construct, focusing not only with the biologies of bodies and tuberculosis bacteria, but also the nature of the social and medical worlds in which those bodies and bacteria were embedded."--